Gendered narratives in Kyrgyz media: exploring social dynamics through the lens of violence - Niyazi Ayhan; Mehrafruz Nabieva (Cogent Social Sciences)
This study investigates the gendered representation of homicides in Kyrgyzstan’s media by analysing news articles published in 2021. Employing statistical data and content analysis, the study explores how male and female homicides are portrayed. The findings suggest that while male homicides are reported more frequently – likely reflecting actual disparities in incidence – they are often framed in ways that reinforce associations between masculinity and violence. In contrast, female homicides tend to be underreported or narratively diminished. These portrayals reinforce patriarchal norms deeply embedded in Kyrgyzstan’s cultural and political structures, reflecting broader issues of gender-based violence in Central Asia. It is crucial to understand the role of media in shaping public perceptions to address these inequalities. The study highlights the media’s potential as a tool for social change, emphasising how balanced and equitable reporting could challenge traditional gender roles and foster societal transformation.